Vulvar pagetoid urothelial intraepithelial neoplasia: a case report. Issue 2 (4th March 2023) - Boret, Stephanie; Lambert, Edward; Charles, Van Praet; Philippe, Tummers; Ponette, Diederik; Darras, Jochen; Mattelaer, Pieter; Verbeke, Sofie; Lumen, Nicolaas; Decaestecker, Karel
Abstract: Background: Pagetoid urothelial intraepithelial neoplasia (PUIN) is a form of secondary Extramammary Paget Disease (EMPD). It is a rare malignant condition seen on the female genitalia synchronous or metachronous with bladder cancer (BC). Case presentation: A 66-year-old female presented with PUIN at the labia minora 2 years after an open anterior pelvic exenteration with ileal conduit urinary diversion for carcinoma in situ (CIS) of the bladder. PUIN of the vulva and vagina was confirmed by a punch biopsy and the patient underwent a radical vaginectomy with urethrectomy and inguinal sentinel node procedure. Immunohistochemically EMPD was identified by the expression tumor protein 63 (p63), cytokeratin 7, and cytokeratin 20 (CK20). Conclusions: PUIN is a rare but distinct clinical entity as a form of secondary EMPD which can be differentiated from primary EMPD based on medical history, histology, and immunohistochemistry.